Cost optimal and zero energy levels in the renovation of residential buildings – Rainha Dona Leonor case study - Almeida, Manuela Guedes de (2014)
Improving energy efficiency in existing buildings is a great challenge. These buildings have their own limitations related with their design, location and function. To study the possibilities of cost-effectively improve the thermal performance of these buildings and increase the chances of reaching the nearly zero energy (nZEB) target, one building of Rainha Dona Leonor neighbourhood has been analysed. The purpose of the study was to analyse the robustness of the cost optimal methodology when renovating towards nZEB targets. With this work it was possible to understand that the most cost effective package of renovation measures to achieve cost optimal levels and to achieve the nZEB target are very similar and these results do not suffer major changes when variations on the energy prices, discount rates or photovoltaic (PV) costs are considered. However, these changes make the use of PV more cost-effective and nZEB levels become, sometimes, also cost optimal levels.